1997
DOI: 10.1002/hlca.19970800111
|View full text |Cite
|
Sign up to set email alerts
|

The Diyne Reaction of 3, 3′‐Bis(phenylethynyl)‐2, 2′‐bithiophene Derivatives via Rhodium Complexes: A novel approach to condensed benzo[2, 1‐b :3, 4‐b′]dithiophenes

Abstract: The syntheses of benzo‐fused benzo[2, 1‐b:3, 4‐b′]dithiophenes 1 and benzo[2, 1‐b:3, 4‐b′:5, 6‐c″]trithiophenes 2 are described. The treatment of easily available 3, 3′‐bis(phenylethynyl)‐2, 2′‐bithiophene derivatives 5a and 6 (via PdII‐catalyzed alkynylation of the corresponding 3, 3′‐dibromo‐2, 2′‐bithiophenes; see Scheme 1) with chlorotris‐(triphenylphosphine)rhodium(I) yields the corresponding cyclic rhodium complexes 7 (Scheme 2) which smoothly react with acetylenes and sulfur to give 1 and 2 in good yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Synthesis and photophysical properties: In a modified procedure reported by Dahlmann and Neidlein, [25] oxidative coupling of lithiated 2,3-dibromobenzo [b]thiophene (1) with copper(II) chloride in diethyl ether at À78 8C gave 3,3'-dibromo-2,2'-diA C H T U N G T R E N N U N G (benzo [b]thiophene)…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Synthesis and photophysical properties: In a modified procedure reported by Dahlmann and Neidlein, [25] oxidative coupling of lithiated 2,3-dibromobenzo [b]thiophene (1) with copper(II) chloride in diethyl ether at À78 8C gave 3,3'-dibromo-2,2'-diA C H T U N G T R E N N U N G (benzo [b]thiophene)…”
Section: Resultsmentioning
confidence: 99%
“…Synthesis and photophysical properties : In a modified procedure reported by Dahlmann and Neidlein,25 oxidative coupling of lithiated 2,3‐dibromobenzo[ b ]thiophene ( 1 ) with copper(II) chloride in diethyl ether at −78 °C gave 3,3′‐dibromo‐2,2′‐di(benzo[ b ]thiophene) ( 2 ). Benzannelated phosphole 3 was obtained in good yield by our general route to dithienophospholes22, 24 by using n BuLi in the presence of N , N , N , N ‐tetramethylethylenediamine to lithiate the 3,3′‐positions, followed by treatment of the dilithio intermediate with phenyldichlorophosphane in diethyl ether at −78 °C (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thieno[ a ]dibenzothiophene derivatives are generally synthesized by (a) Pd‐catalyzed cycloaddition reaction between halo‐benzothiophenes and alkynes, (b) Wilkinson's catalyzed intramolecular cyclization reactions of benzothiophenes, (c) photochromic cyclization reactions of symmetric benzothiophenes, (d) base catalyst intramolecular ring‐closing reactions of benzothiophenes, (e) photochemical cyclization reaction of 3‐alkenyl benzothiophenes . These methods have many disadvantages such as limited derivatives, hard reaction conditions, low yields, expensive catalyst and multi‐step.…”
Section: Introductionmentioning
confidence: 99%
“…The TMS or alkyl substituted alkynes were introduced by Sonogashira reactions to achieve 2a – e in high yields. Then, they were treated with tris(triphenylphosphine) rhodium(I) chloride (Rh(PPh 3 ) 3 Cl, Wilkinson catalyst) to produce rhodium complex intermediates that were converted to the target compounds 3a – e by adding sulfur powder to form the third thiophene ring . We found that (i) Rh(PPh 3 ) 3 Cl needed to be added in equimolar amounts with substrates 2a – e ; (ii) the ring-closure reactions from 2a and 2d with TMS groups to 3a and 3d required refluxing in benzene while the reactions from 2b , 2c and 2e with alkyl chains to 3b , 3c and 3e proceeded smoothly in benzene at room temperature; and (iii) for the purification of 3a , the TMS groups were removed mostly during the silica-gel column separation and three species 3a (20%), 4-trimethylsilylbenzo[2,1-b:3,4-b′:5,6-c″]trithiophene with one TMS (4%), and 4,6-di(trimethylsilyl)-benzo[2,1-b:3,4-b′:5,6-c″]trithiophene with two TMS (8%) were obtained, which made target product 3a achievable directly by the column separation.…”
mentioning
confidence: 99%